Renovating the Richardsons - Smith, Virginia, 1960- (Smith, Virginia, 1960- Tales from the Goose Creek B&B ;, 2016)
Things are finally starting to click in the small town of Goose Creek, Kentucky. Millie Richardson is hard at work renovating a drafty Victorian house into a B&B. Her husband, Al, is busy writing checks for the renovations. But Goose Creek never stays quiet for long. The intra-county softball game is coming up, and Millie volunteers Al as team manager. The team is a disaster. Are they going to embarrass themselves in front of the whole county? As if that weren't enough to keep the town gossips busy, a new business has opened on Main Street, and the ladies are up in arms. Imagine--a massage parlor--in Goose Creek! No decent Creeker will stand for it.